Eyring-Powell nano liquid flow through permeable elongated sheet conveying inclined magnetic field subject to constructive chemical reaction and multiple slip effects - Patil, Vishwambhar S.; Patil, Amar B.; Shamshuddin, MD; Humane, Pooja P.; Rajput, Govind R. (International journal of modelling & simulation, 2023)
The present study examines the multiple slip effects and constructive chemical reaction on Eyring-Powell nanoliquid through a permeable elongated sheet on an inclined magnetic field. The energy balance equation includes Heat and Joule dissipation terms. The renowned Buongiorno nanofluid model is employed extensively to explore the thermophoresis and Brownian motion phenomena. The primary partial differential equations (PDEs) of governing flow phenomena are remodeled to non-linear ordinary differential equations (ODEs) by adopting proper similarity invariants. Runge-Kutta 4 th order quadrature employing shooting technique is utilized to transform boundary value problem to initial value problem to seek numerical results via graphs and tables on physically interesting parameters. Current outcomes are validated through the comparison with previously published studies. An applied magnetic field slows down the fluid and raises both thermal and solutal boundary layers. It is significant to notice that the thermal boundary layer rises, as the Brownian and Thermophoresis are amplified.